OWE-033 Integrating major haemorrhage policies: endoscopy and laboratory working together. (8th June 2018) - Dwyer, Julie; Murray, Audrey; Law, Lisa; MacDonald, Lesley; Hazra, Eleanor; Whyte, Suzanne; Hands, Katherine; Barron, Morag; Groome, Max
Abstract : Introduction: Major haemorrhage is a common medical emergency in endoscopy rooms where on site critical care support is not always standard. Successful management includes resuscitation, appropriate and safe use of blood products alongside effective communication between clinical and laboratory teams. NICE, the National Patient Safety Association and the Serious Hazards of Transfusion organisation all specifically refer to the need for major haemorrhage protocols. NHS Tayside's Blood Transfusion Service launched an updated major haemorrhage policy (MHP) in May 2017. We developed a protocol that combines practical clinical response within both the endoscopy room and the laboratory. We wish to describe the development and implementation of this policy. Methods: A time and space study was completed looking at staff roles within the endoscopy room, typically endoscopist, nurse (RN) and Health Care Assistant (HCA); and the unit as a whole during major GI bleeds. Barriers to effective resuscitation, timely provision of blood products, communication with laboratories/other clinical teams were identified. Results: We identified variation in the following key areas: Staff roles and numbers in room Communication between nursing, medical and laboratory teams Need for a team leader to free up the endoscopist The following protocol was developed. Endoscopist: Declares major haemorrhage. Assesses haemostasis/patients global status, requests additional clinical support (eg anaesthetics). Nursing: Room RN activates in-room buzzer triggering protocol. Three additional RNs and 1 HCA supplement the original room team. RN A (Team Leader) Activates Laboratory MHP via '2222' call, coordinates the room, allocates staff roles, runs resuscitation, communicates with additional teams RN B - assists with therapeutics RN C - patient observations, fluid/medication delivery, scribes HCA A - runner for equipment etc Porter - available throughout Laboratory: '2222' call triggers the laboratory and blood bank to prepare and dispatch: 4 units packed red cells, 4 units fresh frozen plasma and 1 pool of platelets directly to the endoscopy unit by a dedicated porter. The lab remains on standby as required. The policy's introduction was supplemented by training sessions including simulated scenarios to increase staff awareness, confidence and responsiveness to major haemorrhage. Conclusions: We believe this protocol is the first to give a practical description of a process dovetailing clinical and laboratory response to major haemorrhage. Having a clearly defined team leader and standardising individual staff roles allows streamlined communication with other clinical groups in a non critical care environment.